Case Report: Torsade de Pointes Induced by the Third-Generation Epidermal Growth Factor Receptor–Tyrosine Kinase Inhibitor Osimertinib Combined With Litsea Cubeba - Zhang, Xia-yan; Wu, Cha-bin; Wu, Cai-xia; Lin, Li; Zhou, Yue-juan; Zhu, Yan-yan; Tian, Wei-qiang; Luo, Song-mei (Frontiers in Cardiovascular Medicine, 2022)
Torsades de Pointes (TdP) occurred in a 68-year-old female with epidermal growth factor receptor (EGFR) mutant lung cancer administered osimertinib, the third-generation EGFR tyrosine kinase inhibitor (TKI). Electrocardiogram (ECG) recorded at Tdp showed QT prolongation (QTc = 515 ms), to which a Traditional Chinese Medicine (TCM) named “Litsea Cubeba” may have contributed. After discontinuation of osimertinib and Litsea Cubeba, magnesium supplementation, potassium supplementation, lidocaine infusion, and the pacemaker frequency adjustment, Tdp terminated. However, QT prolongation sustained at discharge (QTc = 528 ms), partly because of the emergency use of amiodarone. Osimertinib may prolong the QT interval leading to TdP, especially when multiple risk factors to lengthen QT interval are incidentally overlapped. Thus, regular monitoring of ECG and appropriate management of concomitant drugs are highly recommended.